Persuasive Rhetorical Strategies in Anies Baswedan’s TEDxC40Cities Speech: An Aristotelian Rhetoric Analysis - Nady Chiquitta Putri Assyieffa; Otong Setiawan Djuharie (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study examines the persuasive strategies used by Anies Baswedan in his TEDx speech titled “Governments, Make Public Transport Equitable.” As the Governor of Jakarta, Baswedan delivered the speech on a global platform to advocate for equitable, inclusive, and sustainable public transportation. The research focuses on how he employs Aristotle’s classical rhetorical appeals, namely ethos to establish credibility, pathos to create emotional connection, and logos to present logical reasoning, in order to engage and persuade his audience. Using qualitative rhetorical analysis, the study explores how these appeals are combined and positioned throughout the speech. The official transcript was carefully analyzed to identify statements that reflect each persuasive strategy. The findings show that logos is the most dominant appeal, as Baswedan presents data, measurable goals, and clear policy outcomes. Ethos is conveyed through his position, achievements, and inclusive vision, while pathos emerges in moments where he highlights social justice, the urgency of addressing climate change, and the unifying power of public transport. This research shows that rhetorical appeals in political speeches like Baswedan’s are not applied in a strict sequence but are interwoven to strengthen the overall persuasive impact. The study offers insight into how classical rhetorical strategies are applied in modern communication platforms such as TEDx.